Patient trust and patient safety for low-priority patients: A randomized controlled trial pilot study in the prehospital chain of care. (September 2019) - Norberg Boysen, Gabriella; Christensson, Lennart; Jutengren, Göran; Herlitz, Johan; Wireklint Sundström, Birgitta
Highlights: Low-priority patients were difficult to identify. The ambulance nurse's ability to assess low-priority patients may be questioned. These patients experienced trust regardless if they were referred to CHC or ED. Although trust was experienced, 31% were exposed to limited patient safety risks. Abstract: Background: Patients who call for an ambulance but only have primary care needs do not always get appropriate care. The starting point in this study is that such patients should be assigned to as basic of care as possible, while maintaining high levels of patient trust and patient safety. Aim: To evaluate patient trust and patient safety among low-priority ambulance patients referred to care at either the Community Health Centre (CHC) or the Emergency Department (ED). Methods: This randomized controlled trial pilot study compared the level of patient trust and patient safety among low-priority ambulance patients who were randomized into two groups: CHC (n = 105) or ED (n = 83). Results: There was a high level of trust in the care received, regardless of whether the patient received care at CHC or ED. Overall 31% fulfilled one or more of the given criteria for potentially jeopardizing patient safety. Conclusion: Patient selection for the trial indicated a potential limit in patient safety. There was a high level of trust in the care received regardless of whether the patient received care. The accuracy of patient selection for the new care model needs to be further improved with the intention to enhance patient safety even further.